The effects of burnt cockle shell as graceful awlsnail repellent on green mustard (Brassica rapa) - Nordin, Norhazwani (2013)
Green mustard, Brassica rapa L. locally known by the generic name ‘sawi’ is the most popular leaf vegetable in Malaysia. Several cultivars differentiated by their stem colour, leaf size and flowering habits are grown locally. Problems of sawi cultivation are insect, disease and snails. One of the important snails that attack B. rapa is Graceful Awlsnail (Allopeasgracile). The snail attacks during seedling stages and 1-2 weeks after the green mustard was planted. Application of synthetic molluscicide such as metaldehyde and methiodicarb is an effective ways for controlling snail; however, it can contribute to detrimental effects to environment and biodiversity. Therefore, alternative methods in controlling the snail using natural repellents could help to reduce the negative impact of synthetic molluscicides. Repellents such as neem, tea and coffee have been reported to be effective in controlling snail. However, another cheap repellent, cockle shell has shown to be a promising repellent, although it has not been scientifically reported. The objective of this experiment is to determine the effectiveness of cockle shells as repellent for controlling A.gracile. This experiment was conducted in glasshouse in Field 2 Universiti Putra Malaysia for rearing the snail and Laboratory C, Block E, University Putra Malaysia for repellent study; five treatments of Cockle shell with 5 replications were used. Each replicates consisted of 25 snails. The experiment was arranged in randomized complete block design. Parameter taken was the time for the snail to move away from the burnt cockle shell to the furthest distance in petri dish. The result shown burnt cockle shell is successfully repelled the snail and the amount of cockle shells powder needed is correlated to the stages of the snails with younger stage snails repelled faster compared to later stages snail.